Building the business platform by modularization strategies: Cases of Taiwan social networking vendors - Chia-Liang Hung (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Firms achieve their competitive advantage quickly through the concept framework of open innovation by integrating external inspiration with internal endowment when facing hyper-competition in the digital era. This paper deploys open innovation into building platform blocks by modular operators. These eight modular operators are splitting, augmenting, deleting, substituting, inversing, porting, configuring, and integrating. By means of case studies of two Taiwan Internet vendors, the results depict the manipulation strategies between eight modular operators to fit seven functional requirements for weaving social media, which are presence, identity, sharing, reputation, groups, conversations, and relationship. Finally, this paper advances propositions about the deployment of modularization strategies to develop a competitive platform.
Keywords: 650; e-commerce; innovation; modularization; platform; product design